The history of court interpreting: from Nuremberg to The Hague (70 years of experience) - Berezowski, Łukasz Jan (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The main objective of the article is to set out the historical aspects of cooperation between interpreters and the judiciary in the contemporary era, which is inextricably linked with the most historical events of the 20th century. In this regard, not negligible is the involvement of interpreters in the Nuremberg trials (1945–49) before the International Criminal Tribunal for the former Yugoslavia (1993) and Rwanda (1994) as well as, last but not least, in the foundation of the first permanent criminal tribunal in The Hague (International Court of Justice, ICJ). In conclusion, it is important to emphasize that the character of work as court interpreter, which is apparently corresponding to community interpreting, constitutes a separate category of translation studies given the criteria of high standards and professional ethics.